Simulation study of some PRMA-based protocols with channel reservation for data traffic. (13th February 2007) - Li, Xue Jun; Chong, Peter Han Joo
Medium Access Control (MAC) and resource allocation are two challenging issues in mobile network. Packet reservation multiple access (PRMA) is considered as a promising MAC protocol for future application. In this paper, we first propose a PRMA-based scheme with dynamic channel assignment (DCA) in mobile cellular network. Through computer simulation we show that our proposed scheme outperforms the PRMA schemes with fixed channel assignment (FCA). Then, we propose another technique, namely location-based power transmission, to further improve the performance. This scheme can be extended and optimised for other mobile networks, such as mobile ad hoc networks (MANETs).